Opportunities of using oral intraluminal laser lithotripsy for a large calculus of the common bile duct (clinical report) - Y. V. Ivanov; D. V. Sazonov; A. V. Smirnov; A. V. Mamoshin; A. V. Baranov; D. N. Panchenkov (Biomedical Photonics)
There is a clinical report of successful oral intraluminal laser lithotripsy with subsequent lithoextraction of a large concretion of the common bile duct in a patient with choledocholithiasis and mechanical jaundice. For the intraluminar lithotripsy a tulium laser "Urolaz" was used with energy modes 0,025-0,05-0,1 J, up to a maximum of 0.5 J. The average power is 6-10 W. Laser exposure was carried out by pulses in an aqueous medium in order to prevent carbonation of the light guide and smoke. The effect of exposure to the concretion was manifested in its fragmentation and the formation of small particles without damage of the mucous membrane of the common bile duct. The total duration of the intervention was 45 minutes. The method is effective and safe, thus it avoids the need of endoscopic papillosphincterotomy and violation of the anatomical integrity and physiological function of the Oddi sphincter.